American independent cinema : an introduction - Tzioumakis, Yannis (Edinburgh University Press, 2017)
This introduction to American Independent Cinema offers both a comprehensive industrial and economic history of the sector from the early twentieth century to the present and a study of key individual films, filmmakers and film companies.